Safe Load for Laterally Unsupported Angles - Leigh, J.M.; Thomas, B.F.; Lay, M.G. (Engineering Journal, 1984)
The tables are based theoretically on the constant moment case and use a maximum permissible stress of 0.66Fy, where Fy is the material yield stress. However, for short spans the loads are reduced where necessary to ensure that the maximum permissible shear stresses given in Ref. 1 are not exceeded. The safe loads are applicable for applied loads within half a leg length on either side of the shear centre. The method by which this load is obtained is described under "Calculation of Safe Loads." The safe load shown in the tables is the uniformly distributed load which causes a maximum bending moment equal to the critical constant moment.